Inclusion, Education and Translanguaging How to Promote Social Justice in (Teacher) Education? - Panagiotopoulou, Julie A.; Rosen, Lisa; Strzykala, Jenna (Inklusion und Bildung in Migrationsgesellschaften, 2020)
This open access book is designed as an international anthology on the broader subject of inclusion, education, social justice and translanguaging. Prefaced by Ofelia García, the volume unites conceptional and empirical contributions focusing on various actors within educational institutions, from early childhood to secondary education and teacher training, while offering insights into multiple European and North-American educational systems. ; This open access book is designed as an international anthology on the broader subject of inclusion, education, social justice and translanguaging. Prefaced by Ofelia García, the volume unites conceptional and empirical contributions focusing on various actors within educational institutions, from early childhood to secondary education and teacher training, while offering insights into multiple European and North-American educational systems.